2016
DOI: 10.1371/journal.pone.0166863
|View full text |Cite
|
Sign up to set email alerts
|

Viral Metagenomic Analysis Displays the Co-Infection Situation in Healthy and PMWS Affected Pigs

Abstract: The development of high-throughput sequencing technologies have allowed the possibility to investigate and characterise the entire microbiome of individuals, providing better insight to the complex interaction between different microorganisms. This will help to understand how the microbiome influence the susceptibility of secondary agents and development of disease. We have applied viral metagenomics to investigate the virome of lymph nodes from Swedish pigs suffering from the multifactorial disease postweanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 30 publications
1
49
0
2
Order By: Relevance
“…Surveillance of livestock and the surrounding environment is a hallmark of early detection but is currently targeted to known risks.Advances in Next-Generation Sequencing (NGS) technologies and rapid development of bioinformatics and computational tools offer new opportunities for EID surveillance in quality and in scale. Particularly, metagenomic NGS (mNGS) allows unbiased detection of all microbes and viruses in a sample, showing potential for timely detection of rare or novel infectious etiologies, as well as for surveillance of foodborne and waterborne viruses [20][21][22][23][24][25][26]. However, the use of mNGS as a potential surveillance tool requires a deeper understanding of what is "normal" diversity in humans [27], as well as wildlife [28,29] and farm animals [30].…”
mentioning
confidence: 99%
“…Surveillance of livestock and the surrounding environment is a hallmark of early detection but is currently targeted to known risks.Advances in Next-Generation Sequencing (NGS) technologies and rapid development of bioinformatics and computational tools offer new opportunities for EID surveillance in quality and in scale. Particularly, metagenomic NGS (mNGS) allows unbiased detection of all microbes and viruses in a sample, showing potential for timely detection of rare or novel infectious etiologies, as well as for surveillance of foodborne and waterborne viruses [20][21][22][23][24][25][26]. However, the use of mNGS as a potential surveillance tool requires a deeper understanding of what is "normal" diversity in humans [27], as well as wildlife [28,29] and farm animals [30].…”
mentioning
confidence: 99%
“…Viral metagenomics analysis in healthy and pigs suffering from the postweaning multisystemic wasting syndrome (PMWS) showed that pigs have a considerable viral flora consisting mainly of small single-stranded and circular DNA viruses [13]. Although many viruses were also detected in the healthy pigs, the number of porcine circovirus 2 (PCV2) had increased considerably in the PMWS pigs.…”
Section: The Porcine Viromementioning
confidence: 99%
“…PCV2 can be detected in both healthy and diseased pigs [1] and is found in the lymphatic system in most pigs [2,3].…”
Section: Short Communicationmentioning
confidence: 99%